2017
DOI: 10.1007/s00038-017-1048-4
|View full text |Cite
|
Sign up to set email alerts
|

Social vulnerability as a predictor of physical activity and screen time in European children

Abstract: Migrants and children with unemployed parents are at risk for excessive ST and all vulnerable groups have lower odds of being sports club members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
1
22
0
3
Order By: Relevance
“…Nevertheless, consistent with our results, one study in adults found the OR for MetS was two times higher in those unemployed compared to employed subjects [39]. Unemployment entails anxiety, distress, depression and a decrease in activity in adults [38] that might be felt by children and may worsen their lifestyle factors and mental health and subsequently their MetS risk [12][13][14].…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 4 more Smart Citations
“…Nevertheless, consistent with our results, one study in adults found the OR for MetS was two times higher in those unemployed compared to employed subjects [39]. Unemployment entails anxiety, distress, depression and a decrease in activity in adults [38] that might be felt by children and may worsen their lifestyle factors and mental health and subsequently their MetS risk [12][13][14].…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Another possible explanation on how socioeconomic disadvantages may increase the risk of MetS is its association with unhealthy lifestyle behaviours including overeating, consumption of energy-dense foods, higher sedentary behaviours and lower levels of PA [11][12][13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations